Children entertainment in retail stores. Issue 11 (25th November 2014) - de Faultrier, Brigitte; Deli-Gray, Zsuzsa; Matura, Tamás; Árva, Lászlo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the theoretical background of the involvement and the entertainment of children of four to seven years of age in the purchase process at Hungarian retail stores. It also examines the practice of local and foreign retailers in Hungary. Design/methodology/approach – A review of literature is followed by the description of an exploratory study as well as its findings. The study contained two distinct phases: first 160 retail stores which were selling goods to children (exclusively or together with products for adults) were randomly selected and observed, and then 120 face-to-face or mini group interviews were made with Hungarian children. Findings – At the moment retail store managers in Hungary do not recognise that children can, and often do affect the length of time their parents spend in retail stores and that children also exert influence on their parents' purchase decisions and behaviour. Retail store managers rarely provide any entertainment for children and involve them in the shopping experience and even when they do, they fail to do it in the right way. Also, store personnel do not have the right mentality towards children. The study also reveals that children do not wish to have sophisticated or expensive games during the purchase process, but instead would like to be actively involved in the shopping experience by completing little "missions" or "challenges". Research limitations/implications – On the basis of the research results it becomes clear that creatively designed involvement and entertainment of children in retail stores would encourage families to spend more time spent in retail stores and may serve to increased sales. It would however presume collaboration between retail stores and the producers of toys and creative accessories. Originality/value – The paper aims to address the rarely and sporadically analysed question of how retail managers should entertain and involve young children in the process of shopping. The exploratory study sheds light on the big gap between what is offered by the retail management and what is expected by the young children during shopping in Hungary. It also points to the apparent lack of attention and awareness amongst retailers concerning the influence that children have on parents during the shopping process.